Hybrid (Solo)Self-Employment and Upskilling: Is Online Platform Work a Path Towards Entrepreneurship? - Konstantinos Pouliakas; Antonio Ranieri (Institute of Labor Economics (IZA), 2022)
The increasing use of online labour platforms as intermediaries for finding work – known as crowdwork or gig work – is a new form of 'hybrid' (solo)self-employment that hinges on the borders of dependent and self-employment. In this study we use a novel international dataset of online platform workers, the Cedefop Crowdlearn dataset, to analyse if engagement in hybrid digital self-employment could augment individuals' skills and hence potentially act as a stepping stone towards fuller entrepreneurship. We also examine if a digital proto-entrepreneurial experience is sustainable over time by analysing crowdworkers' satisfaction from their work. The paper's findings provide some support to the hypothesis that hybrid work experiences, especially when platform work is carried out alongside another dependent job, can facilitate additional and varied skill development done via one's secondary platform activity and potentially spur fuller entrepreneurial commitment. However, such skill formation dividends are deficient for part-time hybrids who are mostly driven towards solo self-employment out of necessity, making their journey from proto- to full entrepreneurship less feasible. Our paper provides additional evidence to the marked diversity and hybridity of different forms of (solo)self-employment in modern labour markets.
Keywords: J22; J24; J62; J28; L26; J49; 330; hybrid self-employment; platform/gig economy; crowdworkers; skills; learning; entrepreneurship; digitalisation